Implementation of Criminal Sanctions for Abuse of Government Subsidized Fuel (BBM) Transportation and Trade - K Kuswardani; Antan Yuniar (Proceeding International Conference Restructuring and Transforming Law, 2023)
Fuel oil (BBM) is one of the vital elements needed to serve the needs of the general public. Basically, the government has policies regarding the use of fuel oil. One of them is the existence of subsidized fuel oil. The existence of subsidized fuel oil is due to the consideration that fuel oil is a vital commodity which can cause price increases for other commodities. Subsidized fuel oil is actually given to people from the middle to lower economic groups with the aim of getting fuel oil at cheap prices. However, this subsidized fuel oil sometimes does not meet the government's intended targets. This misuse of subsidized fuel oil is commonly carried out by commercial transport. It is stated in Law Number 22 of 2001 concerning Oil and Natural Gas that processing, transportation, storage and trading business activities can be carried out if a business permit has been obtained from the government. Proven as in case no. 123/Pid.Sus-LH/2022/PNKpg which violates Article 55 of Law Number 22 of 2001 in conjunction with Paragraph 5 number 9 Article 55 of Law Number 11 of 2020 concerning Job Creation by smuggling subsidized kerosene fuel. and diesel. The criminal act of misuse of commercial transportation of fuel oil is regulated in Article 55 of Law No.2/2001. Based on the description above, the problem that can be studied in this paper is identifying the unlawful nature of the criminal act of misuse of commercial transportation of subsidized fuel oil and how criminal sanctions are applied for this act.